Pengaruh Stres terhadap Kadar Glukosa Darah pada Penderita Hiperglikemia - Ida Yohana; Lukman Waris; Marthia Ikhlasiah (Faletehan Health Journal, 2024)
DM sufferers must change their lifestyle to remain blood glucose in their body balanced. The changes can make them vulnerable to stress. The purpose of this study was to determine the effects of stress on blood glucose levels of hyperglycemic patients at Kunciran Baru Health Center area, Tangerang City in 2023. The research method used was quantitative with a nested case control research design. The samples used were 89 respondents who were selected by simple random sampling technique. Stress was measured using the Stress Self-Rating Questionnaire-20. The data were analyzed by T-test. The results showed an increase in the average of blood glucose levels from 2022 (mean 197.97; SD 87.96) to 2023 (mean 232.55; SD 93.04). Most respondents were not stressed (57.3%), the average blood glucose level of the stress group respondents was 274.26 (SD: 97.02), while the average blood glucose level of the non-stressed group was 201.47 (SD: 77.22). The results of the analysis showed a significant difference in blood glucose levels of the two groups of respondents (p value<0.001). The results of this study corroborated previous studies that showed stress as a factor that can affect blood glucose levels of DM sufferers and the stress management ability is important to have in order to maintain normal blood glucose levels.